The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1161/circulationaha.105.563486
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting p90 Ribosomal S6 Kinase Prevents Na + -H + Exchanger–Mediated Cardiac Ischemia-Reperfusion Injury

Abstract: Background-Pharmacological and genetic studies indicate that the Na ϩ -H ϩ exchanger isoform 1 (NHE1) plays a critical role in myocardial ischemia and reperfusion (I/R) injury. We found that p90 ribosomal S6 kinase (RSK) phosphorylated serine 703 of NHE1, stimulating 14 -3-3 binding and NHE1 activity. Therefore, we hypothesized that inhibiting RSK in cardiomyocytes would prevent NHE1 activation and decrease I/R-mediated injury. Methods and Results-To examine the role of RSK in vivo, we generated transgenic mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
0
13

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 32 publications
4
67
0
13
Order By: Relevance
“…U0126 had similar neuroprotection as inhibition of NHE1 activity by HOE 642 or genetic ablation. It has been reported that inhibition of p90 RSK by transgenic expression of a p90 RSK mutant enhances the tolerance of mouse myocardium to ischemia and reperfusion-induced injury, probably through reduced sarcolemmal NHE1 activation (29). This is consistent with our result that activation of the ERKp90 RSK pathway is detrimental and responsible for the activation of NHE1 in ischemic neurons.…”
Section: Nhe1 Activity Is Stimulated In Cortical Neurons Aftersupporting
confidence: 93%
See 1 more Smart Citation
“…U0126 had similar neuroprotection as inhibition of NHE1 activity by HOE 642 or genetic ablation. It has been reported that inhibition of p90 RSK by transgenic expression of a p90 RSK mutant enhances the tolerance of mouse myocardium to ischemia and reperfusion-induced injury, probably through reduced sarcolemmal NHE1 activation (29). This is consistent with our result that activation of the ERKp90 RSK pathway is detrimental and responsible for the activation of NHE1 in ischemic neurons.…”
Section: Nhe1 Activity Is Stimulated In Cortical Neurons Aftersupporting
confidence: 93%
“…A serine/threonine kinase p90 RSK , a downstream substrate of ERK1/2, has been reported to directly phosphorylate NHE1 at Ser 703 in the regulatory C-terminal domain and activate the exchanger activity in response to growth factors (23). Phosphorylation of Ser 703 on NHE1 by p90 RSK creates a binding motif for protein 14-3-3 ␤ (17) and stabilizes NHE1 in an active state in ischemic cardiomyocytes (29).…”
Section: Nhe1 Activity Is Stimulated In Cortical Neurons Aftermentioning
confidence: 99%
“…9 A recent publication suggested that inhibition of the exchanger only after its activation by acidosis, but not during its basal function, may present therapeutic advantages. 11 Although inhibition of the NHE-1 only after critical situations and not under basal conditions seems unrealistic, it was reported that inhibition of p90 ribosomal S6 kinase, which phosphorylates the cytosolic tail of the NHE-1, decreased agonistic activated NHE-1 function without inhibiting its basal homeostatic function. 11 More interestingly, this inhibition was accompanied by beneficial effects.…”
Section: T He Namentioning
confidence: 99%
“…39 Several protein kinases have been shown to be involved in the phosphorylation of NHE1, including PKC, 40,41 ROCK, 42,43 MAPK-dependent pathways, [44][45][46] and p90 rsk . 45,47 The impact of phosphorylation on activity varies, in some cases increasing exchange activity or shifting the pH-dependent activation of NHE1 to more alkaline pH i . 105 In contrast, phosphorylation of the high-affinity calmodulin binding site at Ser-648 by protein kinase B/Akt prevents the NHE1-calmodulin interaction and thus inhibits NHE1 ion transport activity.…”
Section: Mechanisms Controlling Nhe1 Activity and Expression In Pasmcmentioning
confidence: 99%